Utility of prehospital electrocardiogram characteristics as prognostic markers in out-of-hospital pulseless electrical activity arrests. Issue 2 (21st October 2017) - Ho, Michael L; Gatien, Mathieu; Vaillancourt, Christian; Whitham, Veronica; Stiell, Ian G
Abstract : Background: It is unclear if there are predictors of survival, including ECG characteristics, that can guide resuscitative efforts in pulseless electrical activity (PEA) cardiac arrests. We studied the predictive potential of presenting prehospital ECGs on survival for patients with out-of-hospital cardiac arrest (OHCA) with PEA. Methods: We studied prehospital ECGs of patients with OHCA prospectively enrolled between June 2007 and November 2009 at the Ottawa/OPALS (Ontario Prehospital Advanced Life Support Study) site of the Resuscitation Outcomes Consortium PRIMED study (Prehospital Resuscitation using an IMpedance valve and Early versus Delayed analysis). We included adult non-traumatic OHCA with PEA rhythm where resuscitation was attempted. We measured HR, QRS interval and presence of P waves, and determined their impact on return of spontaneous circulation (ROSC) and survival to hospital discharge (SHD) using multivariate regression analysis. Results: The demographic characteristics of the 332 included cases were the following: mean age 71.8, male 58.4%, SHD 5.4% and ROSC at ED arrival 26.5%. Survivors had similar HR (56.8 vs 52.0 beats per minute (bpm), p=0.53) and QRS intervals (128.7 vs 129.6 ms, p=0.95) compared with non-survivors. Prehospital ECG characteristics did not predict SHD or ROSC on multivariate analyses. Patients with initial HR <30 bpm had a 3.8% survival rate; those with both HR <30 bpm and QRS≥120 ms had a 3.7% survival rate. Location of arrest predicted SHD (adjusted OR (AdjOR)=1.49, 1.11 to 1.99; p=0.007). Atropine use negatively predicted SHD (AdjOR=0.06, 0.02 to 0.22; p<0.001). Predictors of ROSC ALS paramedic on scene (AdjOR=8.90, 1.11 to 71.41; p=0.04) and successful intubation (AdjOR=3.35, 1.75 to 6.39; p<0.001). Atropine use negatively predicted ROSC (AdjOR=0.27, 0.14 to 0.50; p<0.001). Conclusions: Presenting prehospital ECG characteristics did not predict SHD or ROSC in OHCA PEA victims and should not be used to guide termination of resuscitation. Location of arrest was a positive predictor for SHD; atropine use was a negative predictor. ALS paramedic on scene and successful intubation were positive predictors of ROSC; atropine use was a negative predictor. Trial registration number: NCT00394706 ; post-results.